Эмпирические исследования налоговых возможностей различных стран - Гурнак, А.В. (Економіка промисловості, 2013)
Проаналізовано і зіставлено методичні підходи й узагальнено результати найбільш важливих емпіричних досліджень податкових можливостей держав на основі багатофакторних економетричних моделей. Показано, що їх еволюція відбувалася на основі урахування все більшої кількості чинників, які здійснюють вплив на податкові можливості держави, у тому числі макроекономічного, соціального, інституціонального, а також демографічного і географічного. Ключові слова: податковий коефіцієнт, податкові можливості, податкові зусилля, множинний регресійний аналіз. Проанализированы и сопоставлены методические подходы и обобщены результаты эмпирических исследований налоговых возможностей государства на основе многофакторных эконометрических моделей. Показано, что их эволюция осуществлялась за счет учета все большего количества факторов, которые оказывают влияние на налоговые возможности государства, в том числе макроэкономического, социального, институционального, а также демографического и географического. Ключевые слова: налоговый коэффициент, налоговые возможности, налоговые усилия, множественный регрессионный анализ. Taxes are the main source of government revenue. Tax ratio, i.e. the ratio of total taxes to GDP or GNP, is the most widely-used measure of taxation level in national economies. Data for different countries show that there is considerable variation in tax ratio level between countries. This has stimulated interest in the study of what determinants really define countries tax ratio. This knowledge has practical importance, because it allows policymakers to evaluate taxable capacity of the country and justify fiscal policy. Taxable capacity is generally interpreted as the predicted tax ratio that can be estimated by regression analyses taking into account country’s specific macroeconomic, demographic and institutional features. Last several decades have yielded a vast number of studies which use empirical models to assess countries tax capacity. This paper surveys a selected number of such works. The purpose of this paper is to analyze, identify and compare methodological approaches and results in the most important empirical studies of tax capacity of the state and evaluate the perspectives of their future development. The evolution of empirical researches has been carried out by taking into account an increasing number of determinants that influence on the country’s tax capacity. In general, despite the existingdifferences, sometimes quite strong, in the results obtained by different researchers, it is clear that the tax capacity of the state is positively related to the level of economic development and foreign trade, dominated by the structure of direct taxes in tax revenue. The structure of the national economy is an important determinant of the level of taxation. There is a negative relationship between the tax rate and the share of the agricultural sector in GDP. Institutional determinant also matters. Confidence in the state, the level of the shadow economy and corruption, situation with property right protection have large influence on countries tax capacity. It should be also agreed that the climatic and geographic characteristics have influenced on the creation of incentives for implementing the commitments of "fiscal contract" between society and state. The paper shows that, in general, using a relatively new method of panel data is not a reason to abandon the earlier results based on the cross-sectional analysis. The paper concludes with a suggestion for future empirical research of tax capacity in various countries. Keywords: tax ratio, tax capacity, tax effort, multiple regression analysis.